Percursos criativos na concepção de Canto de Cravo e Rosa, de Viviane Juguero: a dramaturgia impressa para a leitura da criança - Grazioli, Fabiano Tadeu (2019)
Children's and young adult's Brazilian Literature has contributed to the dramaturgy genre. Especially, the texts that are staged, used for drama reading activities and games. However, just a small number of these books are published and these few publications, which are considered almost rare, have appeared in the publishing market through illustrated books. Considering that the drama genre is only understood by the young adult reader, this process follows the opposite tendency of the drama text, the books are read by children instead of young adults. Moreover, the book Canto de Cravo e Rosa that was written by Viviane Juguero and published in 2009, was chosen to be studied in this doctoral thesis. So, Canto de Cravo e Rosa is the corpus of this research because it makes us reflect about the drama text genre, which has been read by children and it is called in this study: Printed dramaturgy for children's reading. Through this investigation, it will be possible to answer some questions about the drama text. In addition to it, this process will lead us to understand the drama text characteristics, peculiarities, the context in which it is developed and about the creative paths of it. Our research has a qualitative approach and applied nature. The hypothetical-deductive method used in this research is related to the objectives. Furthermore, it is an exploratorydescriptive study and the technical procedure is linked to bibliographic documentary research. Therefore, the path we have chosen starts with the Children's Literature emergence in Europe and Brazil and it is based on the studies of Marisa Lajolo and Regina Zilberman (1985, 1986), Regina Zilberman (2005) and Nelly Novaes Coelho (2000). When it comes to the Literature in the childhood, Peter Hunt (2010) and Fernando Azevedo (2014) were mentioned in order to support the research. Next, the illustrated book was analyzed following the studies of Maria Nikolajeva and Carole Scott (2011) and once more, Peter Hunt (2010). In order to highlight important aspects of Children's Literature, we found the contribution needed through Regina Zilberman (2015), Vera Lúcia Bertoni dos Santos and Ivo Bender (2003), Marco Camarotti (2005), Dib Carneiro Netto (2003, 2014), Bárbara Heliodora (2007), Maria Lucia de Pupo (1991) and Fany Abramovich (1983). In the sequence, we present the theoretical background that has guided the dramaturgy in general and it is inspired by Patrice Pavis (2007, 2008, 2011) in agreement with David Ball (2014), Daniel Furtado Simões da Silva (2013), Ramon Santana de Aguiar (2008), Clarice Lopes Mendes (2009), Décio de Almeida Prado (2007) and Rubem Rocha Filho (1986). Then, there is a space to explore the analysis and the drama text reading, based on the studies of Jean-Pierre Ryngaert (1996, 2013), Luis Paulo Vasconcelos (1987) and Nerina Raquel Dip (2005). All these theoretical aspects are then presented through an epistemological analysis device, which is structured in five stages of execution, marked by specific criteria and indicators. The application of this device allows us to state at the end of the research that Canto de Cravo e Rosa is an example of printed dramaturgy for children's reading. Thus, it is possible to confirm that there is a particular dramaturgy created for children and it can be read through the illustrated book. Finally, this is an important academic contribution, especially because the publishing houses have faced these facts in the last decade.